Individual Versus Group Physical Therapy for Patients with Low Back Pain: Outcomes and Process (Therapeutic Factors). Issue 3 (2nd July 2020) - Netzer, Ofra; Shechtman, Zipora
ABSTRACT: Low back pain (LBP) is a common health problem usually treated individually, and requires costly physical therapy. Group treatment, besides being cost-effective, provides psychological support to the recovery of people who struggle with a physically disabling condition. The current study compares individual and group treatment of LBP, measuring differences in outcomes and process data (therapeutic factors). The study included 158 patients who participated in group ( n = 71) and individual ( n = 87) physical therapy, using a pre-post-follow-up design. Results indicated a significant improvement in all outcome measures at postintervention in both treatment settings, with no difference between them, which were sustained at follow-up. On a clinical level, a few differences were found: At postintervention, minimal clinically important improvement in perceived functioning and level of pain was greater among patients treated individually. On the other hand, at follow-up, only group participants gained additionally in perceived functioning and in fear avoidance. Therapeutic factors of other- versus self-focus and problem definition–change were more prevalent in group treatment.